2014
DOI: 10.1111/ejn.12612
|View full text |Cite
|
Sign up to set email alerts
|

Cortical muscle control of spontaneous movements in human neonates

Abstract: Anatomical studies show the existence of corticomotor neuronal projections to the spinal cord before birth, but whether the primary motor cortex drives muscle activity in neonatal 'spontaneous' movements is unclear. To investigate this issue, we calculated corticomuscular coherence (CMC) and Granger causality in human neonates. CMC is widely used as an index of functional connectivity between the primary motor cortex and limb muscles, and Granger causality is used across many fields of science to detect the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…A signal can be called causal to another one if one can predict a second signal better by incorporating past information from the first signal (Granger, 1969). It is often used to provide information on the direction of coherence and has been used for EEG recordings during walking (Lau, Gwin, & Ferris, 2014) as well as combined recordings of EEG and EMG (Kanazawa et al, 2014).…”
Section: Brain-muscle Linkmentioning
confidence: 99%
“…A signal can be called causal to another one if one can predict a second signal better by incorporating past information from the first signal (Granger, 1969). It is often used to provide information on the direction of coherence and has been used for EEG recordings during walking (Lau, Gwin, & Ferris, 2014) as well as combined recordings of EEG and EMG (Kanazawa et al, 2014).…”
Section: Brain-muscle Linkmentioning
confidence: 99%
“…However, a recent study has shown low‐level but significant CMC between vertex EEG and a leg muscle EMG in newborn infants (Kanazawa et al . ). As the authors of this study pointed out, this finding may be consistent with the presence of functional corticomotoneuronal projections at or shortly after birth, as has been suggested from studies using TMS in neonates (Eyre ).…”
Section: Introductionmentioning
confidence: 97%
“…In the M1 forepaw representation of adult rats, the tactile sensory inputs converge on motor neurons (Chapin and Woodward, 1986), indicating the close interaction of sensory and motor functions even on the basis of single neurons. Such a strong somatosensory input to M1 is considered to be required for coordinated movements (Hikosaka et al, 1985;Xerri et al, 1996;Hiraba et al, 2000;Faraji et al, 2013), motor learning (Ridding et al, 2000;Luft et al, 2002), and sensory processing during active movements (Ferezou et al, 2007;Zagha et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Neuronal activity in different subcortical regions, such as the spinal cord or brainstem (Clarac et al, 2004;Blumberg, 2010;Tiriac et al, 2012), trigger these early motor behaviors, although recent studies provide evidence that, in preterm human babies, activity in the motor cortex contribute to limb movements (Kanazawa et al, 2014). In turn, these spontaneous movements elicit a sensory stimulus that evokes typical activity patterns in the primary somatosensory cortex (S1) of immature rodents and humans (Khazipov et al, 2004;Milh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation